2017
DOI: 10.4314/iijikm.v8i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of demographic factors on knowledge sharing among researchers in selected research institutes in Ibadan, Nigeria

Abstract: Knowledge sharing is an effective means to provide information for organizational growth. The study investigated the influence of demographic factors on knowledge sharing among researchers in selected research institutes in Oyo state, Nigeria. The study adopted survey research method. Total enumeration technique was used to cover all the 440 researchers in the four selected research institutes in Ibadan, Oyo State in Nigeria. Five (5) research questions guided the study and three hypotheses were tested at 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…They publish textbooks and chapters in books, they publish articles in journals, they share their experiences in seminars and workshops, they discuss their projects with peers within and outside the university, they present their knowledge in conferences, symposiums and public lectures, they share knowledge on social media, they share knowledge in departmental, faculty and other university-based meetings, they share teaching materials, they sharing knowledge when on national assignments and share knowledge through mobile phones. This finding is in conformity with that of Lawal, Oriogu and Ogbuiyi (2017) which revealed that the major methods of knowledge sharing among the respondents are through seminars, training, workshop, conferences, social media and online search engines.…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 3 more Smart Citations
“…They publish textbooks and chapters in books, they publish articles in journals, they share their experiences in seminars and workshops, they discuss their projects with peers within and outside the university, they present their knowledge in conferences, symposiums and public lectures, they share knowledge on social media, they share knowledge in departmental, faculty and other university-based meetings, they share teaching materials, they sharing knowledge when on national assignments and share knowledge through mobile phones. This finding is in conformity with that of Lawal, Oriogu and Ogbuiyi (2017) which revealed that the major methods of knowledge sharing among the respondents are through seminars, training, workshop, conferences, social media and online search engines.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…The essence of knowledge sharing is even more desired in universities (Lawal, Oriogu & Ogbuiyi, 2017). Universities need to share knowledge held by employees if they want to benefit from their intellectual capital and compete effectively in the global marketplace (Swart & Kinnie, 2003).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The conclusions from research relating to gender differences in the sphere of the readiness towards KS are not unequivocal. Some research indicates that gender type does not have a significant impact on KS (Chowdhury, 2005;Mogotsi, Boom, Fletcher, 2011;Ojha, 2005;Razmerita, Kirchner, Nielsen, 2016;Watson, Hewett, 2006), while other research confirms the differences in this area (Abukhait, Bani-Melhem, Zeffane, 2019;Boateng, Dzandu, Agyemang, 2015;Grubić-Nešić, Matić, Mitrović, 2015;Miller, Karakovsky, 2005;Lawal, Oriogu, Ogbuiyi, 2017;Lin, 2006;Pangil, Nasrudin, 2008;Tan, Trang, 2017;Taylor, 2004). The research of Lin (2006) indicated that women are more willing to share knowledge as they are more sensitive to instrumental ties and have the need to overcome traditional professional challenges.…”
Section: Literature Review and Research Backgroundmentioning
confidence: 99%